Banksy's subversive gift: A socio-moral test case for the safeguarding of street art. Issue 2 (4th March 2018) - Hansen, Susan
Abstract : This paper discusses the fate of Banksy's (2014) Mobile Lovers which was painted overnight on the door of the Broad Plains Youth Club in Bristol. The subsequent removal of Mobile Lovers from the youth club for safeguarding in the Bristol Museum afforded the work a seemingly neutral zone of protection. However, the museum was also represented as an agent of the city, and as a democratic space, where visitors, as 'the people', were encouraged to record their own preferences for the future of the work. Rancière's conceptualization of democracy as a disruptive process, rather than an established consensual state of affairs, is employed to challenge an understanding of the museum's strategies as self-evidently democratic. Despite the high profile dispute between the youth club and the City of Bristol over who should be considered the proper beneficiary of Banksy's work, it was agreed that it should be considered a 'gift' to the community and should thus be protected. The case of Mobile Lovers sets a socio-moral precedent for the safeguarding of street art, as it represents a novel recognition of the wishes of the community and the intentions of the artist in determining the fate of street art, and a rare acknowledgement of the moral rights of street artists to determine the first distribution of their work, over the rights of property owners, who are otherwise able to claim the tangible artworks on their walls as individual, rather than community, property. Ultimately, the perception of street art in socio-moral terms as a 'gift' enabled an orientation to, and subversion of, the legal strictures currently prohibiting the recognition of the moral rights of street artists.